Selection and Improvement of Product Formulae for Best Performance of Quantum Simulation - Morales, Mauro E.S.; Costa, Pedro C.S.; Pantaleoni, Giacomo; Burgarth, Daniel K.; Sanders, Yuval R.; Berry, Dominic W. (Quantum Information & Computation, 2025)
Quantum algorithms for simulation of Hamiltonian evolution are often based on product formulae. The fractal methods give a systematic way to find arbitrarily high-order product formulae, but result in a large number of exponentials. On the other hand, product formulae with fewer exponentials can be found by numerical solution of simultaneous non-linear equations. It is also possible to reduce the cost of long-time simulations by processing, where a kernel is repeated and a processor need only be applied at the beginning and end of the simulation. In this work, we found thousands of new product formulae, and numerically tested these formulae, together with many formulae from prior literature. We provide methods to fairly compare product formulae of different lengths and different orders. For the case of 8th order, we have found new product formulae with exceptional performance, about two orders of magnitude better accuracy than prior work, both in the processed and non-processed cases. The processed product formula provides the best performance due to being shorter than the non-processed product formula. It outperforms all other tested product formulae over a range of many orders of magnitude in system parameters T (time) and ϵ (allowable error). That includes reasonable combinations of parameters to be used in quantum algorithms, where the size of the simulation is large enough to be classically intractable, but not so large it takes an impractically long time on a quantum computer.
CRIS-Team Scopus Importer:2025-05-30
Keywords: product formula; quantum algorithm; quantum simulation; symplectic integrator; Trotter formula